Pendampingan Remaja dalam Upaya Pencegahan Perilaku Bullying di Dukuh Kupang Karangdowo - Ratna Agustiningrum; Agustina, Nur Wulan; Handayani, Sri; Irawan AM, Ady; Rozani, Moh (Institut Citra Internasional, 2024)
This bullying often occurs in various school and communities, even in educational institutions and in the community. Bullying refers to behavior that is carried out repeatedly by a person who is weaker with the aim of hurting that person. Violence is still often found in schools and in society. Research conducted by sejiwa (2018). States that there are 27 % of teachers who believed that bullying is normal and legitimate behavior, teachers even think that verbal bullying is a common thing that occurs in social situations. Other data states thah 13.1% of students are perpetrators of bullying (Sulistyowati, 2022). The problems that teenagers who are victims of bullying are more likely to suffer from include the emergence of various mental problems such as depressions, anxiety and sleep problems which may carry over into, adulthood, physical health complaints, such as headaches, stomach aches and muscle tension, feelings of insecurity when being in the school environment and a decrease in enthusiasm for learning and academic achievement. In quite rare cases, teenage victims of bullying may show violent traits.